Cell interaction between compartments establishes the proximal-distal axis of Drosophila legs. - Diaz-Benjumea, F.J.; Cohen, B.; Cohen, S.M. (Nature, 1994)
The appendage primordia of Drosophila are subdivided into compartments by the localized expression of transcription factors. Interaction between cells in adjacent compartments establishes organizing centres responsible for generating spatial pattern and promoting cell proliferation in the developing appendages. Localized expression of hedgehog (hh) in the posterior compartment of the leg imaginal disc directs expression of wingless (wg) in ventral-anterior cells and decapentaplegic (dpp) in dorsal-anterior cells near the anterior-posterior compartment boundary; wg then acts to specify ventral cell fate and to organize the dorsal-ventral axis of the leg. Interaction between wg-expressing ventral cells and dorsal cells near the anterior-posterior compartment boundary promotes axis formation in the leg. Here we show that the combined action of wg-expressing cells in the ventral-anterior compartment and dpp-expressing cells in the dorsal-anterior compartment activates expression of Distal-less, a gene required for proximal-distal axis formation in the limbs. These results demonstrate that sequential interaction between anterior-posterior and dorsal-ventral compartments establishes the proximal-distal axis of the limbs.